RESEARCH ON STRESS SPECTRUM GROUPING METHOD OF HIGH SPEED EMU BOGIE - CHEN DaoYun; LIU DeKun; SUN ShouGuang; LI Qiang (Jixie qiangdu)
The determination of structural dynamic stress spectrum is of great significance in the structural fatigue strength evaluation as well as reliability design.To evaluate structure of fatigue strength accurately,stress history on fatigue key parts of motor bogie framework was obtained through dynamic stress test of high-speed EMU on actual operation line.Fatigue damage values per kilometer of stress spectra with different grouping numbers were calculated using equidistant grouping method and Palmgren-Miner linear cumulative damage theory.Then,the effect of different group number on fatigue damage was analyzed.The results show that when the grouping number is small,it can lead to deviation of fatigue damage.As the grouping number increasing,damage decreasing,and tends to the theoretical value.This phenomenon can be interpreted by the EMU framework dynamic stress characteristic of small stress cycles high concentration.Meanwhile,an unequal distance grouping method was presented which is applicable to framework structure stress spectrum.The study can provide the basis for framework structure design.